2018
DOI: 10.1007/s00424-018-2111-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of variations in dietary Pi intake on intestinal Pi transporters (NaPi-IIb, PiT-1, and PiT-2) and phosphate-regulating factors (PTH, FGF-23, and MEPE)

Abstract: Hyperphosphatemia is a common condition in patients with chronic kidney disease (CKD) and can lead to bone disease, vascular calcification, and increased risks of cardiovascular disease and mortality. Inorganic phosphate (P) is absorbed in the intestine, an important step in the maintenance of homeostasis. In CKD, it is not clear to what extent P absorption is modulated by dietary P. Thus, we investigated 5/6 nephrectomized (Nx) Wistar rats to test whether acute variations in dietary P concentration over 2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Different species display diverse mechanisms for intestinal absorption of phosphate, and therefore the understanding of human intestinal phosphate handling is incomplete [34].…”
Section: Intestinal Handling Of Phosphatementioning
confidence: 99%
See 3 more Smart Citations
“…Different species display diverse mechanisms for intestinal absorption of phosphate, and therefore the understanding of human intestinal phosphate handling is incomplete [34].…”
Section: Intestinal Handling Of Phosphatementioning
confidence: 99%
“…In healthy humans, 60-75% of dietary phosphorus is absorbed [4,21]. Paracellular transport involves passive diffusion of phosphate through tight junctions and occurs independently of any regulatory hormones [34]. The type II sodium-phosphate cotransporter, Npt2b (SLC34A2), and type III cotransporters, PiT1 and PiT2, modulate transcellular transport in the intestine.…”
Section: Intestinal Handling Of Phosphatementioning
confidence: 99%
See 2 more Smart Citations
“…The so called ‘intestinal phosphatonin’ was suggested to act independently of changes in plasma phosphate concentration or parathyroid hormone (PTH) [5]. The finding that matrix extracellular phosphoglycoprotein (MEPE), a protein typically secreted from bone [53] that has a phosphaturic effect on the kidney [59], is present in the intestinal epithelium, specifically the duodenum [3, 47], led to the suggestion that this may be the factor proposed by Berndt et al [47]. However, subsequent studies were unable to confirm the existence of this intestinal phosphatonin, but instead found that acute renal adaptation to an oral phosphate load requires PTH [40, 62].…”
Section: Napi-iib and The Gut-renal Axismentioning
confidence: 99%